A Radical Pastoral Theology for the Anthropocene Era: Thinking and Being Otherwise - LaMothe, Ryan (Journal of pastoral theology, 2021)
The Anthropocene Age will usher in more frequent natural and political disasters. These looming catastrophes invite critically reimaging our theologies. This article sketches out a radical pastoral theology for the Anthropocene Era by first addressing and illustrating the existential dynamics of care. Here it is claimed that care is radical because it founds agency, as well as subjectivity and intersubjectivity. This sets the stage to demonstrate the connection to the political reality of care and its connection to other species and nature. The concluding section builds on the previous sections, while shifting to the theological rendering of radical care as the indeterminate, infinite care of a non-sovereign God revealed in creation and in the ministry of Jesus Christ.